2009
DOI: 10.1007/s10201-009-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of water colors in a shallow acidified lake, Lake Onneto, Japan, using colorimetric analysis and bio-optical modeling

Abstract: Lake Onneto has unusually brilliant water colors, such as blue-green, green, and greenish yellow. We investigated the coloration mechanism in this lake by measuring the radiometric water color and inherent optical properties (IOPs), such as attenuation, absorption, and scattering coefficients of color-producing agents (CPAs) in the lake. The hue of the water body was determined using colorimetric analysis. In addition, the radiometric water color of the lake was simulated using bio-optical modeling. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Onda et al . [26] who investigated the cloudy emerald-green hue of Yugama Crater Lake on Mount Shirane, Japan, reported that the water color is due to an optical interaction involving Rayleigh and Mie scattering by colloidal sulfur particles, causing blue and cloudy white colors, respectively, and absorption by dissolved iron (II) ions cause a green color [9], [26].…”
Section: Resultsmentioning
confidence: 99%
“…Onda et al . [26] who investigated the cloudy emerald-green hue of Yugama Crater Lake on Mount Shirane, Japan, reported that the water color is due to an optical interaction involving Rayleigh and Mie scattering by colloidal sulfur particles, causing blue and cloudy white colors, respectively, and absorption by dissolved iron (II) ions cause a green color [9], [26].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the b * axis describes the blue (negative values) to yellow (positive values) transition [ Schanda , 2007]. We adopted this color coordinate system because it had an advantage over other indices, such as the CIE xyY color space [see Duntley , 1963; Oyama and Shibahara , 2009; Tyler , 1964], in that it includes a component for lightness. This greatly differentiated the waterbodies of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…For natural waterbodies, measurements of their above‐water apparent optical properties (AOP) can be converted into colorimetric coordinate values, which may provide a quantitative means to test the relationship between color and specific limnological variables. This approach offers a potentially useful tool for resource management (e.g., for assessments of aesthetic value and water quality); however, it has been applied to only a limited extent to date [ Duntley , 1963; Oyama and Shibahara , 2009; Tyler , 1964].…”
Section: Introductionmentioning
confidence: 99%
“…The blue water index and other color space values in our study were obtained from radiometric observations with high spectral resolution. Radiometric analysis has been used to quantify the apparent color of other natural waters (Bukata et al ; Bukata et al ; Oyama and Shibahara ; Watanabe et al ), and has multiple advantages over traditional visual matching of color samples. First, it avoids any observational error derived from ambient conditions and perceptional differences among observers (Davies‐Colley et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The geometry of radiometric measurements for color evaluation of natural water bodies varies among studies (Bukata et al 1997(Bukata et al , 2001Davies-Colley et al 1997;Oyama and Shibahara 2009;Watanabe et al 2011), and these differences in methodology will need to be considered when making comparisons. A standardized method with the possibility of broader application is therefore to be preferred.…”
Section: Discussionmentioning
confidence: 99%